Application of Risk Management In Shipyards Based SNI IEC/ISO 31010:2016 on New Shipbuilding Projects - Yusup, Muhammad Firdaus Bin (Maritime Park: Journal of Maritime Technology and Society, 2022)
Shipbuilding in the shipyard needs to be analyzed for risk management to minimize and take action to avoid risk. Risk management techniques in SNI IEC/ISO 31010:2016, namely the consequence and probability matrix. This study aims to identify hazards in new construction works and determine the level of consequences and the probability of a risk arising. This research's benefit is knowing the danger and risk level category. This study uses qualitative research and data collection techniques through in-depth interviews or direct observation in the field. The results showed 14 hazards from 3 jobs: plate cutting, welding, and lifting. The risk analysis scale shows a very high risk (priority I). The high risk (priority II), medium-high risk (priority III), low risk (priority IV), and shallow risk (priority V) in new construction works.